2015
DOI: 10.1038/nsmb.3062
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of the Rubisco-assembly chaperone Raf1

Abstract: Biogenesis of the photosynthetic enzyme Rubisco, a complex of eight large (RbcL) and eight small (RbcS) subunits, requires assembly chaperones. Here we analyzed the role of Rubisco accumulation factor1 (Raf1), a dimer of ∼40-kDa subunits. We find that Raf1 from Synechococcus elongatus acts downstream of chaperonin-assisted RbcL folding by stabilizing RbcL antiparallel dimers for assembly into RbcL8 complexes with four Raf1 dimers bound. Raf1 displacement by RbcS results in holoenzyme formation. Crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
95
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 71 publications
(66 reference statements)
8
95
0
1
Order By: Relevance
“…Cell extracts with confirmed soluble RbcL presence were additionally separated under non-denaturing conditions and probed with anti-RbcL or anti-RAF1 antibodies. Synechocystis RAF1 promoted folding of its own RbcL resulting in formation of a complex exhibiting a migration pattern similar to those reported for T. elongatus (Kolesinski et al 2014), or S. elongatus PCC 7942 (Hauser et al 2015) RbcL 2 -RAF1 2 (Fig. 6b).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Cell extracts with confirmed soluble RbcL presence were additionally separated under non-denaturing conditions and probed with anti-RbcL or anti-RAF1 antibodies. Synechocystis RAF1 promoted folding of its own RbcL resulting in formation of a complex exhibiting a migration pattern similar to those reported for T. elongatus (Kolesinski et al 2014), or S. elongatus PCC 7942 (Hauser et al 2015) RbcL 2 -RAF1 2 (Fig. 6b).…”
Section: Resultssupporting
confidence: 79%
“…In addition, it effectively showed the same function toward RbcLs from two other cyanobacteria ( T. elongatus and S. elongatus PCC 7942). However, in these cases only larger complexes resembling those identified previously as RbcL 8 –RAF 8 (Hauser et al 2015) were observed. Interestingly, spontaneous formation of a presumed octamer was observed for RbcL from T. elongatus alone.…”
Section: Resultsmentioning
confidence: 42%
See 2 more Smart Citations
“…However, advances in engineering precise changes in model systems continue to provide important developments that are increasing our understanding of Rubisco catalysis (Spreitzer et al, 2005;Whitney et al, 2011aWhitney et al, , 2011bMorita et al, 2014;Wilson et al, 2016), regulation (Andralojc et al, 2012;Carmo-Silva and Salvucci, 2013;Bracher et al, 2015), and biogenesis (Saschenbrecker et al, 2007;Whitney and Sharwood, 2008;Lin et al, 2014b;Hauser et al, 2015;Whitney et al, 2015).…”
mentioning
confidence: 99%